On Coc-Preopen Sets in Topological Spaces - A. Salih, Ahmed; J. Ali, Haider (Al-Nahrain Journal of Science, 2024)
In this research we introduced a new concept, which is coc-preopen set, with some properties, theorems, and functions related to this concept. We also benefited from the properties of some spaces in order to find new results related to the concept of coc-preopen.